ANALISIS BIBLIOMETRIK PENELITIAN PEMASARAN DIGITAL SEKTOR PARIWISATA - Alhally, Arafat (ANALISIS, 2025)
This study examines trends and developments in digital tourism marketing research over the past five years using a bibliometric approach. The growing integration of digital marketing within the tourism sector, driven by the global wave of digital transformation, underscores the need to understand its evolving scholarly landscape. Data were collected from Google Scholar using the keyword tourism digital marketing for the period 2020-2024, resulting in a dataset of 998 documents. The analysis employed Publish or Perish and VOSviewer software to explore patterns of research productivity, citation impact, and thematic clustering. The findings revealed seven major thematic clusters covering topics such as social media utilization, consumer behavior, destination branding, and the adoption of advanced technologies including artificial intelligence and virtual reality. Results indicate that digital tourism marketing research is inherently multidisciplinary and continues to broaden its thematic scope in line with the rapidly shifting global digital ecosystem. This study demonstrates the value of bibliometric analysis in identifying research gaps and guiding future scholarly inquiry. The implications are particularly relevant for the formulation of adaptive, inclusive, and context specific strategies for digital based tourism development.